Avoiding the subject : media, culture and the object - Clemens, Justin (Amsterdam University Press, 2004)
What can Roger Rabbit tell us about the Second Gulf War? What can a woman married to the Berlin Wall tell us about posthumanism and inter-subjectivity? What can DJ Shadow tell us about the end of history? What can our local bus route tell us about the fortification of the West? What can Reality TV tell us about the crisis of contemporary community? And what can unauthorized pictures of Osama Bin Laden tell us about new methods of popular propaganda? These are only some of the thought-provoking questions raised in -Avoiding the Subject,- which highlights the feedback-loops between philosophy, technology, and politics in today's mediascape.